Efektivitas Unit Pelaksanaan Teknis Pusat (UPTP) Balai Latihan Kerja Makassar Dalam Mengatasi Pengangguran Di Kota Makassar - Alfira Herman (Pustaka Digital Indonesia, 2023)
The purpose of this study is to determine the effectiveness of the UPTP (BLK) Work Training Center in Overcoming Unemployment in Makassar City. This study uses qualitative research methods, the data used are primary data obtained from interviews with employees at UPTP BLK Makassar and secondary data obtained from agencies related to research. The technique of collecting data using interview, observation and documentation methods. The data analysis method used is descriptive qualitative. The results of this study indicate effectiveness in overcoming unemployment in the city of Makassar and it can be concluded that the Job Training Center is quite effective in overcoming unemployment. This can be seen from table 4.4 which is quite effective in overcoming unemployment in the city of Makassar with the results of research from 2020-2022 that the number of training participants at UPTP BLK Makassar is 74%.